Observation of transition from superfluorescence to polariton condensation in CsPbBr3 quantum dots film - Danqun Mao; Linqi Chen; Zheng Sun; Min Zhang; Zhe-Yu Shi; Yongsheng Hu; Long Zhang; Jian Wu; Hongxing Dong; Wei Xie; Hongxing Xu (Light: Science & Applications, 2024)
Abstract The superfluorescence effect has received extensive attention due to the many-body physics of quantum correlation in dipole gas and the optical applications of ultrafast bright radiation field based on the cooperative quantum state. Here, we demonstrate not only to observe the superfluorescence effect but also to control the cooperative state of the excitons ensemble by externally applying a regulatory dimension of coupling light fields. A new quasi-particle called cooperative exciton-polariton is revealed in a light-matter hybrid structure of a perovskite quantum dot thin film spin-coated on a Distributed Bragg Reflector. Above the nonlinear threshold, polaritonic condensation occurs at a nonzero momentum state on the lower polariton branch owning to the vital role of the synchronized excitons. The phase transition from superfluorescence to polariton condensation exhibits typical signatures of a decrease of the linewidth, an increase of the macroscopic coherence as well as an accelerated radiation decay rate. These findings are promising for opening new potential applications for super-brightness and unconventional coherent light sources and could enable the exploitation of cooperative effects for quantum optics.